The Conservation Management of Engenho Uchôa Wildlife Refuge as a Natural Heritage - Moura, Célio Henrique Rocha; Araujo, Felipe Moura Hemetério; Albuquerque, Caio Coelho Silva (Revista Nacional de Gerenciamento de Cidades, 2021)
From the perspective of United Statian preservationism, where the presence of human beings in areas understood as natural was opposed, the first protected areas in Brazil appear at the threshold of the discussion on the protection of the country's ecosystems, where the dichotomy between man and nature is admitted, and through which instruments for the management of Brazilian biomes and ecosystems are developed. This article discusses the nature management model in Brazil, contrasting traditional management (through the provisions of the National System of Conservation Units / SNUC and which reverberates to State and Municipal Systems) and the conservation management, understood as the modality of management that acts on the patrimonial dimension of nature. This discussion permeates the definitions of Natural Significance, Conservation and Natural Heritage in the Australian Natural Heritage Charter (IUCN, 2002), and through the example of the Mata do Engenho Uchôa Wildlife Refuge (RVSMEU), a state conservation unit by the State System of Conservation Units of Pernambuco / SEUC, it is discussed how the current ecosystem management plan approaches and distances itself from the conservation management of its heritage values.